Civic education and citizenship studies in culture, identity, and art - Sulistyarini Sulistyarini; Jagad Aditya Dewantara; Muhammad Mona Adha (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2023)
Over the past few years, culture has played an essential role in shaping civic culture in multicultural countries that adhere to the nation-state system, such as Indonesia. Culture makes an excellent contribution to support the nation's noble values, traditions, and norms that inspire forms of citizenship in civic culture. We need to think about civic education and the study of citizenship in the scope of culture, identity, and the arts. However, strangely, there has been no effort made by academic actors to study culture, identity, and art in certain areas in the aspect of forming civic culture. Culture, identity, and art are the primary sources of inspiration for a country that adheres to a multicultural system and a nation-state to create social norms for its citizens. The issue is expected to cover as many aspects of customary law, culture, art, and nature as possible and be reported as scientific findings. Authors and scholars from all relevant disciplines are invited to contribute, and we are interested in your research contribution to pertinent illustrations of the fields of civic education and civic studies. The editorial team reviews the specific and cultural roles, identities, and traditional arts as described in the forms of customary law and norms in multicultural societies, performing arts where local culture and identity play an essential role, literature, and folklore in society and history engraved on reliefs. Reliefs such as temples in Yogyakarta, books such as Sutasoma, and the like. We want researchers to write about how culture, identity, and art have played a role in the essential parts of citizenship from the past to the present. In essence, this Special Editorial accommodates writers and academics to conceptualize the role, philosophy, customary law, tradition, norms, and artistic aesthetics as forming civic culture in a country that adheres to the nation's system so that it becomes a new form of knowledge that can be taken for civic education and studies, citizenship itself